Philology the forgotten origins of the modern humanities - Turner, James 1946- (Princeton, New Jersey Princeton University Press, 2014)
Many today do not recognize the word, but "philology" was for centuries nearly synonymous with humanistic intellectual life, encompassing not only the study of Greek and Roman literature and the Bible but also all other studies of language and literature, as well as religion, history, culture, art, archaeology, and a more. In short, philology was the queen of the human sciences. How did it become little more than an archaic word? In Philology, the first history of Western humanistic learning as a connected whole ever published in English, James Turner tells the fascinating, forgotten story of how the study of languages and texts led to the modern humanities and the modern university. This compelling narrative traces the development of humanistic learning from its beginning among ancient Greek scholars and rhetoricians, through the Middle Ages, Renaissance, and Enlightenment, to the English-speaking world of the nineteenth and early twentieth centuries. Turner shows how evolving researches into the texts, languages, and physical artifacts of the past led, over many centuries, to sophisticated comparative methods and a deep historical awareness of the uniqueness of earlier ages. But around 1800, he explains, these interlinked philological and antiquarian studies began to fragment into distinct academic fields. These fissures resulted, within a century or so, in the new, independent "disciplines" that we now call the humanities. Yet the separation of these disciplines only obscured, rather than erased, their common features. The humanities today face a crisis of relevance, if not of meaning and purpose. Understanding their common origins - and what they still share - has never been more urgent. -- from dust jacket
Includes bibliographical references (pages 453-507) and index.
Keywords: Philology -- History; Historical linguistics; Humanities